Wound drainage following groin dissection for malignant disease in adults. - Thomson, DR; Sadideen, H; Furniss, D (2014)
BACKGROUND: Groin dissection is commonly performed for the treatment of a variety of cancers, including melanoma, and squamous cell carcinoma of the skin, penis or vulva. It is uncertain whether insertion of a drain reduces complication rates, and, if used, the optimum time for drain removal after surgery is also unknown. OBJECTIVES: To assess the current level of evidence to determine whether placement of a drain is beneficial after groin dissection in terms of reducing seroma, haematoma, wound dehiscence and wound infection rates, and to determine the optimal type and duration of drainage following groin dissection if it is shown to be beneficial. SEARCH METHODS: In September 2014 we searched the following electronic databases using a pre-designed search strategy: the Cochrane Wounds Group Specialised Register; The Cochrane Central Register of Controlled Trials (CENTRAL) (The Cochrane Library). In November 2013 we searched Ovid MEDLINE; Ovid MEDLINE (In-Process and Other Non-Indexed Citations); Ovid EMBASE and EBSCO CINAHL. We did not restrict the search and study selection with respect to language, date of publication or study setting. SELECTION CRITERIA: We considered all randomised controlled trials (RCTs) comparing wound drainage with no wound drainage in individuals undergoing groin dissection, where the most superior node excised was Cloquet's node (the most superior inguinal lymph node). No limits were applied to language of publication or trial location. Two review authors independently determined the eligibility of each trial. DATA COLLECTION AND ANALYSIS: Two review authors, working independently, screened studies identified from the search; there were no disagreements. MAIN RESULTS: We did not identify any RCTs that met the inclusion criteria for the review. AUTHORS' CONCLUSIONS: There is a need for high quality RCTs to guide clinical practice in this under-researched area.